The proportion of bone mineral density in children with high risk acute lymphoblastic leukemia after 6- and 12-month chemotherapy maintenance phase - Mira Christiyani Santoso; Endang Windiastuti; Alan R. Tumbelaka (Paediatrica Indonesiana, 2010)
Background Low bone mineral density (BMD) value is one of the current concerns in acute lymphoblastic leukemia (ALL) patients. Some risk factors including use of chemotherapeutic drugs, nutritional status, phy sical activities, and progression of disease are suspected as the predisposing factors for development of osteopenia and osteoporosis.Objectives To obtain the proportion of BMD z-score, level of calcium ions, and 25 (OH)D3 in children 'With high risk ALL after 6 and 12 months chemotherapy maintenance phase.Methods We conducted a cross-sectional comparative study from May 2008 to May 2010. Subjects were high risk ALL patients aged 5-18 years old who had completed the 6 or 12 months chemotherapy maintenance phase. We measured 25 (OH) D3 level, calcium ion level, and BMD using electro chemi-luminescence immunoassay, ion selective electrode, and dual x-ray absorptiometry, respectively.Results There were 40 subjects who enrolled this study. The incidence of hypocalcemia and vitamin D deficiency were 33/40 and 40/40, respectively. The mean calcium ion levels, 25 (OH)D3 level, and BMD zô€score values in six months groups were 1.1 (0.1 SD) mmol/L, 21.3 (2 SD) ng/L, -0.7 (0.8 SD), respectively, while in the 12 months group, the values were 1.1 (0.0 SD) mmol/L, 21(2.2 SD) ng/L, -1.7 (0.6 SD), respectively (P=0.478). Body mass index (BMI) and corticosteroid cumulative dose is correlated \\lith the low BMD values in L1-L4.Conclusion The bone mineral metabolism disorder marked with the low levels of calcium, 25 (OH)D3 and osteopenia was observed in ALL patients who underwent chemotherapy. The proportion of the BMD z-score value, calcium ion level, and 25 (OH) D3 in the two groups were not statistically significant.